Oxford graduates' perceptions of a global health master's degree: a case study - Cole Donald; Plugge Emma (BMC, 2011)
Abstract Introduction Low and middle-income countries suffer an ongoing deficit of trained public health workers, yet optimizing postgraduate education to best address these training needs remains a challenge. Much international public health education literature has focused on global capacity building and/or the description of innovative programmes, but less on quality and appropriateness. Case description The MSc in Global Health Science at the University of Oxford is a relatively new, full-time one year master's degree in international public health. The programme is intended for individuals with significant evidence of commitment to health in low and middle income countries. The intake is small, with only about 25 students each year, but they are from diverse professional and geographical backgrounds. Given the diversity of their backgrounds, we wanted to determine the extent to which student background influenced their perceptions of the quality of their learning experience and their learning outcomes. We conducted virtual or face-to-face semi-structured individual interviews with students who had graduated from the course at least one year previously. Of the 2005 to 2007 intake years, 52 of 63 graduates (83%) were interviewed. We used thematic analysis to analyze the data, then linked results to student characteristics. Discussion The findings from the evaluation suggested that all MSc GHS graduates who spoke with us, irrespective of background, appreciated the curriculum structure drawing on the strengths of a small, diverse student group, and the contribution the programme had made to their breadth of understanding and their careers. This evaluation also demonstrated the feasibility of an educational evaluation conducted several years after programme completion and when graduates were 'in the field'. This is important in ensuring international public health programmes are relevant to the day-to-day work of public health practitioners and researchers in low and middle-income countries. Conclusions Feedback from students, when they had either resumed their positions 'in the field' or pursued further training, was useful in identifying valuable and positive aspects of the programme and also in identifying areas for further action and development by the programme's management and by individual teaching staff.